2021
DOI: 10.1038/s41420-021-00423-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase inhibitors exert distinct effects on patient-derived 2D and 3D glioblastoma cell culture models

Abstract: Current therapeutic approaches have met limited clinical success for glioblastoma multiforme (GBM). Since GBM harbors genomic alterations in cyclin-dependent kinases (CDKs), targeting these structures with specific inhibitors (CDKis) is promising. Here, we describe the antitumoral potential of selective CDKi on low-passage GBM 2D- and 3D models, cultured as neurospheres (NSCs) or glioma stem-like cells (GSCs). By applying selective CDK4/6i abemaciclib and palbociclib, and the more global CDK1/2/5/9-i dinacicli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…Interference of CDKi/SpyADI with mitochondria (increased mitochondrial reactive oxygen species (ROS) production and mitochondrial membrane potential) and lysosomal formation were studied based on our previous observations under CDKi monotherapy [ 16 ]. Mitochondrial activity increased cell line-specific after SEQ-dinaciclib/SpyADI or SEQ-abemaciclib/SpyADI treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interference of CDKi/SpyADI with mitochondria (increased mitochondrial reactive oxygen species (ROS) production and mitochondrial membrane potential) and lysosomal formation were studied based on our previous observations under CDKi monotherapy [ 16 ]. Mitochondrial activity increased cell line-specific after SEQ-dinaciclib/SpyADI or SEQ-abemaciclib/SpyADI treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hallmark of genomic instability in GBM is related to perturbations in the S-phase and G2/M transition, with the cyclin D1-CDK4/6-Rb pathway being mostly altered [ 15 ]. Just recently, we described the successful elimination of patient-derived two-dimensional (2D)- and three-dimensional (3D)-cultured GBM cells by the global CDKi dinaciclib as well as the selective CDK4/6 inhibitor abemaciclib [ 16 , 17 ]. The aforementioned CDKi even interfered with the tryptophan catabolism and had complex effects at both the morphological and molecular levels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has profound biological effects. In a very recent study on patient-derived glioblastoma models, we described the CDKi-induced loss of mitochondrial function in pioneering work, characterized by a multivacuolar phenotype and signs of early-methuosis [ 60 ]. Methuosis, a non-apoptotic cell death phenotype, is defined by the accumulation of large fluid-filled cytoplasmic vacuoles that originate from macropinosomes [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the topic on non-DDR signalling kinases that impact the DDR, Riess and colleagues recently assessed targeting of the CDK family of signalling kinases given their common dysregulation in glioblastoma and the recent advancement of a new generation of clinically approved compounds [195]. Using a CDK-based monotherapy approach in various 3D glioblastoma preclinical models, they showed that CDK inhibitors could negatively affect tumour growth, but also that some CDK inhibitors were able to effectively combine with DNA damaging regimes such as radiation and temozolomide treatments.…”
Section: Indirect Ddr Targeting Strategies In Glioblastomamentioning
confidence: 99%
“…Using a CDK‐based monotherapy approach in various 3D glioblastoma preclinical models, they showed that CDK inhibitors could negatively affect tumour growth, but also that some CDK inhibitors were able to effectively combine with DNA damaging regimes such as radiation and temozolomide treatments. However, they also showed that not all tested CDK inhibitors behaved in the same way, with some conferring antagonistic properties when combined with temozolomide, potentially through differential effects on global gene expression patterns [ 194 ]. This study further highlights the need to understand the intricate functional interplay and regulatory mechanisms within the DDR as part of preclinical studies to help maximise the therapeutic potential of such new combinatorial regimes within the clinic.…”
Section: Targeting Functional Interplay Within the Glioblastoma Ddr Networkmentioning
confidence: 99%